InGaN/Dilute-As GaNAs Interface Quantum Well for Red Emitters - Tan, Chee-Keong (Sci Rep, 2016)
The design of InGaN/dilute-As GaNAs interface quantum well (QW) leads to significant redshift in the transition wavelength with improvement in electron-hole wave function overlap and spontaneous emission rate as compared to that of the conventional In(0.2)Ga(0.8)N QW. By using self-consistent six-band k·p band formalism, the nitride active region consisting of 30 Å In(0.2)Ga(0.8)N and 10 Å GaN(0.95)As(0.05) interface QW leads to 623.52 nm emission wavelength in the red spectral regime. The utilization of 30 Å In(0.2)Ga(0.8)N/10 Å GaN(0.95)As(0.05) interface QW also leads to 8.5 times enhancement of spontaneous emission rate attributed by the improvement in electron-hole wavefunction overlap, as compared to that of conventional 30 Å In(0.35)Ga(0.65)N QW for red spectral regime. In addition, the transition wavelength of the interface QW is relatively unaffected by the thickness of the dilute-As GaNAs interface layer (beyond 10 Å). The analysis indicates the potential of using interface QW concept in nitride-based light-emitting diodes for long wavelength emission.